(untitled) (Journal of Dhaka National Medical College & Hospital, 2014)
Introduction: Health care quality is a global issue. The health care industry is undergoing a rapid transformation to meet the increasing needs and demands of its patient population. Hospitals should recognize the demands and health care choice of educated consumers. Patient satisfaction has become an established outcome indicator of quality and efficiency of health care system. Objectives: To assess certain domains of patient satisfaction with services in a private medical college hospital outside Dhaka and to find out the socio demographic variables. Materials & Method: A cross- sectional survey was conducted among the parents of paediatric patients attending a private medical college hospital after taking permission from ethical committee, authority. A pretested, semi structured questionnaire was used for study. Results: Most 253 (77.6%) of the respondents agreed that doctors office provide everything needed for complete medical care. Majority 234 (71.8 %) of the respondents strongly agreed that they can get the medical care without being set back financially. Most (98.5%) of the respondents agreed that they got medical care whenever needed. More than half (60%) of the respondents were satisfied about medical care received and 36% respondents were dissatisfied. Most (81.9%) of the respondents were satisfied with time spent by doctors, 72.1% were satisfied with accessibility and convenience to medical care, 53.9% respondents were satisfied with technical quality, 52.1% were satisfied with communication and 47.7% respondents were generally satisfied. Majority (51.2%) of the respondents were dissatisfied with financial aspect, 48.9% were generally dissatisfied, 45.7% were dissatisfied with interpersonal manner, 44.2% were dissatisfied with communication and 42.6% were dissatisfied with technical quality The comparison of average scored value between age, sex, education, occupation and income showed no significant differences. J. Dhaka National Med. Coll. Hos. 2014; 20 (02): 33-39